2015
DOI: 10.1016/j.ajpath.2014.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Low Expression of miR-126 Is a Prognostic Marker for Metastatic Clear Cell Renal Cell Carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC) is an aggressive tumor with unpredictable behavior. Clinical parameters are not always accurate for predicting prognosis. miR-126 is differentially expressed in many cancers, including RCC, and is down-regulated in metastatic versus primary ccRCC. We assessed the prognostic significance of miR-126 in 264 primary ccRCCs. We also compared its expression in normal kidney, primary and metastatic ccRCC, and RCC subtypes. We validated our results on an independent set of 481 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 63 publications
(50 reference statements)
3
45
0
1
Order By: Relevance
“…A total of 262 cases of primary and metastatic ccRCC (250 primary and 12 metastatic) were analysed, as detailed in our previous publications 27. Formalin-fixed paraffin-embedded tissues were collected from St Michael's Hospital, and University Health Network, Toronto, Canada.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 262 cases of primary and metastatic ccRCC (250 primary and 12 metastatic) were analysed, as detailed in our previous publications 27. Formalin-fixed paraffin-embedded tissues were collected from St Michael's Hospital, and University Health Network, Toronto, Canada.…”
Section: Methodsmentioning
confidence: 99%
“…We performed target prediction analysis using TargetScanHuman 6.2 (http://www.targetscan.org/) and miRecords (http://c1.accurascience.com/miRecords/) software, as in our previous publications 27. We further filtered the predicted gene targets list through literature search and pathway analysis using DIANA-mirPath (http://diana.imis.athena-innovation.gr/DianaTools/index.php?r=mirpath/index) and the Gene Functional Classification tool from DAVID Bioinformatics database (http://david.abcc.ncifcrf.gov/gene2gene.jsp).…”
Section: Methodsmentioning
confidence: 99%
“…miRNA expression changes have been demonstrated in many types of cancer, suggesting their potential values in cancer diagnosis, prognosis and treatment. Up- or down-regulated miRNA expression levels in RCC have been described and reviewed in recent literature [810]. Certain key molecules for ccRCC, such as HIFα, VEGF and mTOR, are possible targets of these dysregulated miRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…A significant increase in circulating miR-126 has been detected in patients with acute myocardial infarction and angina whereas miR-126 downregulation has been reported in plasma from patients with diabetes, heart failure, or cancer [14]. Hence, circulating miR-126 can be modulated by diverse stimuli inducing dissimilar cellular fates in different cell types [60, 85, 9397]. Most recently, Italian researchers demonstrated that circulating miR-126-3p (see Chap.…”
Section: Mir-143/145 Vs Mir-126 Master Regulators Of Vsmc and Ec Fumentioning
confidence: 99%